Cytotoxic and apoptotic potential of gemini-chrysophanol nanoparticles against human colorectal cancer HCT-116 cell lines - Alaadin M. Naqishbandi (BMC, 2022)
Abstract Background Colorectal cancer is among the most common cancers and accounts for nearly 9% of all cancers in the world. Chrysophanol ﻿is a naturally occurring anthraquinone exerts a number of ﻿pharmacological activities ﻿such as anti-inflammation, anti-cancer, ﻿anti-bacterial, anti-viral, and anti-oxidant effects. ﻿This study aims to ﻿produce a novel gemini chrysophanol nanoparticles (Gemini-Chr NPs), and ﻿to evaluate its anti-cancer effect on the human colorectal cancer cell lines. Methods Gemini-Chr NPs were synthesized through nanoprecipitation method and characterized by dynamic light scattering and scanning electron microscopy, ﻿Anti-cancer activities were examined through MTT assay on HCT-116 cancer cells, apoptosis was investigated via Annexin V-FITC/PI dual stain assay. Furthermore, the expression of Bax, Bcl-2 and P53 genes were evaluated using real-time PCR and western blotting assay. ﻿ Results The average particle diameter of the synthesized Gemini-Chr NPs and zeta potential were recorded as 120 nm and 14.4 mV, respectively. In comparison to the normal cells, the cytotoxicity assay confirmed that Gemini-Chr NPs preferentially killed colorectal cancer cells via induction of apoptosis. ﻿Moreover, Gemini-Chr NPs could upregulate the expression of Bax in both cancerous and normal cells (p ≤ 0.05) and decreasing the Bcl-2 expression in only tumor cells (p ≤ 0.01), while the expression of P53 is modulated in tumor cells (p ≤ 0.05). Conclusions Gemini surfactants could be considered for efficient delivery and improvement of anti-cancer effect of chrysophanol. Gemini-Chr NPs might have the potential for developing novel therapeutic agent against colorectal cancer.